2004
DOI: 10.1080/09500340408235278
|View full text |Cite
|
Sign up to set email alerts
|

A high-performance integrated single-photon detector for telecom wavelengths

Abstract: Abstract. We have integrated a commercial avalanche photodiode (APD) and the circuitry needed to operate it as a single-photon detector (SPD) onto a single PC-board. At temperatures accessible with Peltier coolers (~200-240K), the PCB-SPD achieves high detection efficiency (DE) at 1308 and 1545 nm with low dark count probability (e.g. ~10 -6 /bias pulse at DE=20%, 220 K), making it useful for quantum key distribution (QKD). The board generates fast bias pulses, cancels noise transients, amplifies the signals, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Our fits perfectly match the data within rms deviation of < 0.03%. Extracted efficiencies of 20%, and conditional afterpulsing probability in the range of 0.01 -0.03 for 250 kHz trigger rate (device dependent) are similar to the values reported in manufacturer tests performed at the conventional low power regime of =0.1 [4]. We found that in the cw regime the afterpulsing is somewhat stronger and decays faster with the characteristic time of 2.5-3s, which is shorter than the 4-5s measured for pulsed laser.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our fits perfectly match the data within rms deviation of < 0.03%. Extracted efficiencies of 20%, and conditional afterpulsing probability in the range of 0.01 -0.03 for 250 kHz trigger rate (device dependent) are similar to the values reported in manufacturer tests performed at the conventional low power regime of =0.1 [4]. We found that in the cw regime the afterpulsing is somewhat stronger and decays faster with the characteristic time of 2.5-3s, which is shorter than the 4-5s measured for pulsed laser.…”
Section: Introductionsupporting
confidence: 80%
“…To ensure proper operation of SPDs, various approaches for testing SPD have been developed. Modern advanced methods such as the interleaved bias method [4] and the time-interval analysis method [5] permit extraction of both the afterpulsing probability and the detector efficiency. However, these methods rely on complicated timing control schemes and extremely low input power levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the earliest techniques, developed at IBM in the late 1990s, is illustrated in Fig. When properly designed and implemented, this approach strongly suppresses the gate transient and allows the discrimination of small avalanche signals, on the order of 200 fC, reducing afterpulsing [153]. This circuit uses inverting and noninverting reflections from the ends of coaxial cables to generate an opposing pair of gate transients that cancel in a passive network.…”
Section: Cancellationmentioning
confidence: 99%
“…Operating detectors in gated mode has now become an avenue to increase the bit rate for single photon applications, thanks to the significant evolution of this technology over the past decade [4][5][6][7][8][9]. We have developed a self-differencing (SD) circuit [7], which compares the APD output with its identical copy but temporally translated by an integer number of clock cycles, removing the periodical capacitive response of the APD and thus allowing detection of extremely weak avalanches which would otherwise be obscured.…”
mentioning
confidence: 99%